THE UTILIZATION OF 900 WP OFF-GRID SOLAR POWER PLANT FOR PRODUCT INTENSIFICATION OF A HYDROPONICS FARMER GROUP - Rizki Putra Prastio; Prisma Megantoro; Syamsul Arifin; Dimas Dzaky Rafii Muhammad; Irsyad Hilmi; Sigit Dani Perkasa (Jurnal Layanan Masyarakat, 2023)
In collaboration with a group of hydroponics farmers, an activity as a part of community service implementation has been carried out in Pasuruan, Eastern Java. The activity aims to develop a 900 Wp solar power plant capable of providing energy for running the essential electrical devices for the hydroponics system uninterrupted. This idea is to resolve the energy issue when the outage occurs. Moreover, the reliance on the public grid also adds additional expense for the electricity bill. Based on the observation, the power plant reliably provides sufficient energy to turn on different hydroponics electrical devices. It can supply energy for 12 hours without charging to activate, in total, 160 Watt of diverse loads all night long. While during the day, solar panels deliver energy for the batteries recharging and the other loads. Some other facilities are also developed in this activity, including UV plastic roof and addition of the grow lights to promote the plants’ growth acceleration. The plastic roof efficiently reduces the sunlight intensity to lower the heat experienced by the plants, transmits specific wavelengths crucial for growth, and prevents the rainwater from entering the nutrient water tank. Meanwhile, the grow lights stimulate faster growth and quickly recover the plants after receiving much heat that causes them to look wilt. As a result, the farmers are now less reliant on the public grid, and the hydroponics system is more weather-resistant.